Exploring The Significance Of Leadership Development Experiences Of Female Elementary School Supervisors In East Sumba - Tanti Sugiharti Singgih (Journal of Economic and Leadership, 2024)
This study explores the leadership development experiences of female elementary school supervisors, aiming to shed light on the unique challenges and opportunities they encounter in their professional journey. The findings reveal a complex interplay of gender dynamics, mentorship relationships, and organizational culture in influencing their leadership development. Despite facing gender-based obstacles, female supervisors highlighted the significance of supportive networks, continuous professional learning, and resilience as pivotal to their growth as leaders. This literature review study also identifies a lack of gender-specific leadership development programs and calls for more inclusive approaches that recognize and address the unique needs of female educational leaders. The implications of this research extend to policy-making and leadership training programs, suggesting the necessity for systemic changes that promote gender equality and empower female leaders in the educational sector. By understanding the specific experiences of female elementary school supervisors, this study contributes to the broader discourse on leadership diversity and paves the way for more equitable leadership development practices.